PENGARUH JUMLAH PENDUDUK, INFLASI, DAN CADANGAN DEVISA TERHADAP IMPOR BERAS DI INDONESIA PERIODE TAHUN 1988-2017 - Anak Agung Ketut Ayuningsasi, Ni Wayan Ary Suandari (E-Jurnal Ekonomi Pembangunan Universitas Udayana, 2021)
The purpose of this study was to determine the effect of population, inflation, and foreign exchange reserves simultaneously or partially on rice imports in Indonesia. The data used in this study are secondary data obtained from the publication of the Indonesian Central Statistics Agency (BPS) and The World Bank. The results of this study concluded that the population, inflation, and foreign exchange reserves simultaneously had a significant effect on rice imports in Indonesia in the period 1988-2017. This shows that the rise and fall of rice imports in Indonesia is influenced by variables of population, inflation and foreign exchange reserves. The total population does not have a significant effect on rice imports in Indonesia in the period 1988-2017. Foreign exchange reserves partially did not significantly influence rice imports in Indonesia in the period 1988-2017. This happens because the increasing imports made by a country will reduce the foreign exchange reserves owned by the country.